PESAN MORAL DALAM SERIAL KARTUN ANIMASI UPIN DAN IPIN EPISODE “ISTIMEWA HARI IBU” - Haryanto, Dwi (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2017)
This research discusses the moral message contained in animated cartoon series of Upin and Ipin, episode "Mother Day Special" to the learning process of children through the mass media of television as a medium of learning aid. This study aims to find out how the use of mass media television and the extent to which the mass media affect the public, especially children. The results of this study indicate that in the animated series Upin and Ipin, episode "Mother Day Special", there are some moral messages such as honesty, expressions of affection, love, appreciation, and gratitude. Other results indicate that mass media can be used as a medium of learning aids and greatly affect people’s lives, especially children.